(3dCWYeI GdeQVis - (3eMeO Hf YHO Gddg GdHZOGOjs; (3jYbhH Hf ESMGb GdeSjMj Gdedcj GdcQcj GHf Gdba, CHh GdaQL,J (B685 (3g` s ((3eOjfI WhS s)
(3ChdgG (B:s
(3Ef CMOi GdYdhe GdJi jfJaY HgG GdfGS Yde GdWH hgh ef LedI LedI GdYdhe GdSjGSI s
(3BNQgG (B:s
(3hSf ef GdCSfGf hYfO ZdHI cd gNdW ef GdCNdGW s
(3GdfSNI HgG MhGTs
(3cKjQI GdghGeT hGdebUGJs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdChd (B- (3U (B16 s
Keywords: (3GdWHs